2015
DOI: 10.4049/jimmunol.1401762
|View full text |Cite
|
Sign up to set email alerts
|

Modulating DNA Methylation in Activated CD8+ T Cells Inhibits Regulatory T Cell–Induced Binding of Foxp3 to the CD8+ T Cell IL-2 Promoter

Abstract: We have previously demonstrated that CD4+CD25+ Treg cells activated during the course of FIV infection suppress CD8+ CTL function in a TGFβ-dependent fashion, inhibiting IFNγ and IL2 production, and inducing G1 cell cycle arrest. Here, we describe the molecular events occurring at the IL2 promoter leading to suppression of IL2 production. These experiments demonstrate that FoxP3 induced by lentivirus-activated Treg cells in the CD8+ target cells binds to the IL2 promoter, actively repressing IL2 transcription.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…Among the many achievements, these efforts led to approval of an effective FIV vaccine in 2002. Recent studies have addressed important issues such as mechanisms of FIV transmission, replication and evolution [ 22 , 23 , 24 , 25 , 26 , 27 ], FIV vaccine efficacy [ 28 , 29 ], the role of neutralizing antibodies in disease progression [ 28 , 30 , 31 ], virus assembly and release [ 32 , 33 ], viral latency and eradication strategies [ 34 , 35 , 36 ], development of adjunctive therapies [ 37 , 38 , 39 , 40 ], immunology [ 41 , 42 , 43 , 44 , 45 ], interactions with the microbiome [ 46 , 47 ], development of antiretroviral compounds [ 48 , 49 , 50 ] and development of protocols for assessing feline cognitive function [ 51 , 52 , 53 , 54 ]. Many of these efforts are summarized in this volume and in a review by Bienzle [ 55 ].…”
Section: Fiv Infection Of the Nervous Systemmentioning
confidence: 99%
“…Among the many achievements, these efforts led to approval of an effective FIV vaccine in 2002. Recent studies have addressed important issues such as mechanisms of FIV transmission, replication and evolution [ 22 , 23 , 24 , 25 , 26 , 27 ], FIV vaccine efficacy [ 28 , 29 ], the role of neutralizing antibodies in disease progression [ 28 , 30 , 31 ], virus assembly and release [ 32 , 33 ], viral latency and eradication strategies [ 34 , 35 , 36 ], development of adjunctive therapies [ 37 , 38 , 39 , 40 ], immunology [ 41 , 42 , 43 , 44 , 45 ], interactions with the microbiome [ 46 , 47 ], development of antiretroviral compounds [ 48 , 49 , 50 ] and development of protocols for assessing feline cognitive function [ 51 , 52 , 53 , 54 ]. Many of these efforts are summarized in this volume and in a review by Bienzle [ 55 ].…”
Section: Fiv Infection Of the Nervous Systemmentioning
confidence: 99%
“…Our research group has studied the molecular events responsible for CD8 + T cell dysfunction in the FIV model. Data by our lab and others suggest that FIV provirus and infected CD4 + T cells are epigenetically modulated during infection and that epigenetic modulators can be used to reverse these events [ 25 , 115 ]. We have further demonstrated that dysfunctional CD8 + T cells, that evolve during the chronic phase of FIV infection, are epigenetically modulated [ 115 ].…”
Section: Epigenetic Modulation Of Immune Cells As a Results Of Hiv mentioning
confidence: 99%
“…Our group has previously reported that, in the FIV model, lentivirus activated CD4 + CD25 + Treg cells signal via membrane bound TGF-β/Smad signaling to induce Foxp3 in CD8 + T cell targets [ 113 , 114 ]. We have also demonstrated that Foxp3 mediates antiviral cytokine suppression by directly binding to IL-2, TNF-α and IFN-γ promoter region in the acute and chronic phase of FIV infection [ 107 , 115 , 116 ]. Figure 2 B summarizes our findings demonstrating Treg-mediated CD8 + T cell suppression in the FIV model.…”
Section: Cd8 + T Cell Suppression By Cd4 mentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation of T-cell populations: Peripheral blood mononuclear cells ( PBMCs ) from FIV + or FIV − cats were surface stained with CD4-APC and CD25-FITC and sorted into CD4 + CD25 − and CD4 + CD25 + T cell populations (>95% purity) as previously reported [ 24 , 25 ].…”
Section: Experimental (Materials and Methods)mentioning
confidence: 99%